On Some Culture-Specific Issues of TEFL in Armenia - Paronyan, Shushanik (Armenian Folia Anglistika, 2015)
The present article focuses on the cultural aspect of globalization in Armenian higher education system which has come to the fore recently within the framework of the unifying European academic field. Bearing in mind that education is part of culture, some effective ways of adapting teacher-centered educational strategy to Armenian academic network are discussed. Using the cultural dimensions model proposed by G. Hofstede, I make an assumption that certain attitudes and behaviour types characteristic of educational strategies implemented in Armenia recently should be acculturized.